Postoperative troponin increases after noncardiac surgery are associated with raised neurofilament light: a prospective observational cohort study. (April 2021) - Sanders, Robert D.; Craigova, Lenka; Schessler, Benjamin; Casey, Cameron; White, Marissa; Parker, Margaret; Kunkel, David; Blennow, Kaj; Zetterberg, Henrik; Pearce, Robert A.; Lennertz, Richard
Abstract: Background: Myocardial and neuronal injury occur commonly after noncardiac surgery. We examined whether patients who had perioperative myocardial injury (PMI) also incurred neuronal injury, and whether myocardial and neuronal injury were associated with similar changes in inflammatory markers or overlapping clinical predictors. Methods: A total of 114 individuals >65 yr old were recruited from two ongoing perioperative cohort studies (NCT02926417; NCT03124303). Plasma samples were collected before and daily after surgery to process assays for troponin I (PMI), neurofilament light (NfL; neuronal injury) and multiplexed plasma cytokines (inflammation). The primary outcome was the change in NfL in individuals with PMI (>40 pg ml −1 increase in troponin above preoperative values). We conducted logistic regression to identify if there were shared clinical predictors for myocardial and neuronal injury. Results: Ninety-six patients had paired NfL and troponin data. Twenty-three of 94 subjects (24%) with PMI had greater increases in NfL (median [inter-quartile range, IQR]: 29 pg ml −1 [3–95 pg ml −1 ]; 2.8-fold increase) compared with subjects with no troponin increase (8 pg ml −1 [3–20]; 1.3-fold increase; P =0.008). PMI was associated with increased interleukin (IL)-1ra ( P =0.005), IL-2 ( P =0.045), IL-8 ( P =0.002), and IL-10 ( P <0.001). Logistic regression showed that intraoperative hypotension was associated with PMI ( P =0.043). Preoperative stroke ( P =0.041) and blood loss ( P =0.002), but not intraoperative hypotension, were associated with increased NfL. Conclusions: Postoperative troponin increases were associated with changes in NfL and inflammatory cytokines. Increases in troponin, but not NfL, were associated with intraoperative hypotension, suggesting differences in the mechanisms contributing to neuronal and myocardial injury.